2011
DOI: 10.1017/s1466046611000330
|View full text |Cite
|
Sign up to set email alerts
|

Research Article: Hispanics and Environmental Voting in the US Congress

Abstract: We compare the environmental voting behavior of Hispanic congressional members with those of White and African American members, seek to explain disparities in long-term voting trends, and discuss the implications for future environmental policy development. We analyzed congressional members' voting behavior from 1995 to 2006. Multivariate regression models were employed to determine what factors explain racial disparities in voting. Hispanic members were more likely than White, but less likely than African Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Studies tracking changes in attitudes over time also found that minorities support higher levels of spending on the environment than whites and that minority legislators are more likely to vote for environmental bills than other legislators (Ard and Mohai 2011;Taylor 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Studies tracking changes in attitudes over time also found that minorities support higher levels of spending on the environment than whites and that minority legislators are more likely to vote for environmental bills than other legislators (Ard and Mohai 2011;Taylor 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Whites (Ballew et al, 2019; Campbell et al, 2022). Similar heightened environmental concerns are reflected among elected officials, with Hispanic and African American members of Congress more likely than White members to vote proenvironmentally (Ard & Mohai, 2011).…”
Section: Social Psychological and Structural Obstacles To Coalition-b...mentioning
confidence: 91%